Cobalt(II)/(III) complexes bearing a tetradentate thiosemicarbazone: Synthesis, experimental and theoretical characterization, and electrochemical and antioxidant properties - KOCA, ATIF (WILEY, 2020)
New cobalt complexes,Co1andCo2, were synthesized starting from acetylacetone-S-methylthiosemicarbazone. The square planar cobalt(II) and octahedral cobalt(III) complexes were characterized by FT-IR, UV-visible,H-1 NMR, and X-ray diffraction spectroscopies and mass spectrometry. Frontier orbitals of the complexes were theoretically obtained to better understand the complex structures and intermolecular interactions. The electrochemical behaviors ofCo1andCo2were investigated and the results were evaluated by comparing with each other and with similar published compounds to determine their possible usage in various electrochemical technologies, such as energy storage devices, electrocatalysts, and electrosensors. Metal-based oxidation at around 0 V and metal-based reduction at around -1.0 V indicated that these complexes are valuable for the proposed applications. By determining the trolox equivalent antioxidant capacity and the radical scavenging activity of the cobalt complexes, the compatibility between the antioxidant qualification, redox, and theoretical calculation results was discussed.
Keywords: antioxidant potential; cobalt complexes; density functional theory; electrochemistry; thiosemicarbazone; TRANSITION-METAL-COMPLEXES; SCHIFF-BASE; CRYSTAL-STRUCTURE; STRUCTURAL-CHARACTERIZATION; LIGANDS. SYNTHESIS; OPTICAL-PROPERTIES; NICKEL(II); COPPER(II); IRON(III); OXOVANADIUM(IV)